2014
DOI: 10.1161/circimaging.114.001658
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Elastin Deficit in a Marfan Mouse Aneurysm Model Using an Elastin-Specific Magnetic Resonance Imaging Contrast Agent

Abstract: Background-Ascending aortic dissection and rupture remain a life-threatening complication in patients with Marfan syndrome. The extracellular matrix provides strength and elastic recoil to the aortic wall, thereby preventing radial expansion. We have previously shown that ascending aortic aneurysm formation in Marfan mice (Fbn1) is associated with decreased aortic wall elastogenesis and increased elastin breakdown. In this study, we test the feasibility of quantifying aortic wall elastin content using MRI with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…Importantly, Q-VD-OPh treatment also significantly reduced aortic diameter at 3, 4, 5 and, 6 weeks in the Fbn1 C1039G/+ mice although the diameters remain greater than WT control ( Figure 2C), confirming that apoptosis participates in the pathogenesis of early aneurysm development. Although we have reported increased aortic wall thickness in Fbn1 C1039G/+ versus WT mice at 32 weeks, 8 no significant difference was detected at 2 to 6 weeks. Moreover, no difference in wall thickness was distinguished when comparing Q-VD-OPh versus vector control-treated Fbn1 C1039G/+ mice (data not shown).…”
Section: Treatment Of Fbn1contrasting
confidence: 68%
“…Importantly, Q-VD-OPh treatment also significantly reduced aortic diameter at 3, 4, 5 and, 6 weeks in the Fbn1 C1039G/+ mice although the diameters remain greater than WT control ( Figure 2C), confirming that apoptosis participates in the pathogenesis of early aneurysm development. Although we have reported increased aortic wall thickness in Fbn1 C1039G/+ versus WT mice at 32 weeks, 8 no significant difference was detected at 2 to 6 weeks. Moreover, no difference in wall thickness was distinguished when comparing Q-VD-OPh versus vector control-treated Fbn1 C1039G/+ mice (data not shown).…”
Section: Treatment Of Fbn1contrasting
confidence: 68%
“…A more detailed examination of this approach can be seen in our previous study [11] the basic results of which are corroborated in the present study. Recently an MRI-based study was performed with LMI1174—a gadolinium-based elastin-specific magnetic resonance contrast agent (ESMA) which accurately measures elastin bound gadolinium within the aortic wall [48]. In this study they found that in the 8 month Fbn1 C1039G/+ MFS mouse, there was a significant decrease in aortic wall elastin compared to WT.…”
Section: Resultsmentioning
confidence: 97%
“…The authors used an elastin-specific magnetic resonance imaging contrast agent to monitor the AAAs by assessing the elastin content within the ascending aortic aneurysm wall. MRI based on targeted probes was able to detect advanced, but not early, aneurysms 34 . An imbalance in collagen deposition/degradation, especially Col-I, is a key factor in the prognosis of AAAs 35 .…”
Section: Discussionmentioning
confidence: 99%